2010
DOI: 10.1038/modpathol.2009.184
|View full text |Cite
|
Sign up to set email alerts
|

The presence of JC virus in gastric carcinomas correlates with patient's age, intestinal histological type and aberrant methylation of tumor suppressor genes

Abstract: JC virus (JCV) is a neurotropic polyomavirus and the causative agent of progressive multifocal leukoencephalopathy. A role for JCV in gastrointestinal malignancies has been recently suggested. This study was carried out to determine the prevalence of polyomaviruses including JCV, BKV and SV40 in gastric cancers in Tunisia and to determine the clinicopathological characteristics of virus-associated gastric carcinomas. The presence of polyomaviruses DNA sequences was surveyed in 61 cases of primary gastric carci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
2
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 40 publications
1
23
2
2
Order By: Relevance
“…In this study only two samples (1 GC and 1 GA) were positive for JCPyV LTag sequences. Our result reveals a very low frequency of JCPyV LTag sequences in GC and other gastroduodenal diseases, which is inconsistent with a number of other reports [15,23,36]. One possible explanation for this inconsistency is the high percentage of FFPE samples in our GC group (67.9%); the detection rate of JCPyV DNA sequences could be significantly reduced in FFPE samples [15,38].…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…In this study only two samples (1 GC and 1 GA) were positive for JCPyV LTag sequences. Our result reveals a very low frequency of JCPyV LTag sequences in GC and other gastroduodenal diseases, which is inconsistent with a number of other reports [15,23,36]. One possible explanation for this inconsistency is the high percentage of FFPE samples in our GC group (67.9%); the detection rate of JCPyV DNA sequences could be significantly reduced in FFPE samples [15,38].…”
Section: Discussioncontrasting
confidence: 57%
“…Another plausible explanation could be geographic and ethnic variations in JCPyV distribution. The JCPyV LTag sequence was detected in 26.0% of Tunisian GC patients [36]. In addition, 57.0% of Korean [23] and 86.3% of Japanese [15] GC patients harbored the JCPyV LTag sequence in their neoplastic tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, Bofill-Mas, et al showed that viral particles isolated from sewage remained intact after treatment at a pH of 1 for 30 minutes, indicating that ingestion of contaminated water or food may be sufficient for JCV infection of the gastrointestinal tract [20]. Many studies since, have demonstrated the presence of JCV genomic sequences and the expression of T-Antigen in tissues from gastrointestinal tumors, including esophageal carcinoma [11], gastric carcinoma [12], [21], [22], sporadic adenomatous polyps [23], and colorectal adenocarcinomas [10], [24][30].…”
Section: Introductionmentioning
confidence: 99%
“…More recently, JCV was also found in non-neural cancers, such as gastric [9] and lung cancers [10]. JCV infection was first reported as a potential risk factor for colorectal cancer (CRC) in a work by Laghi et al [11], which found that 96% of CRC tissues were positive for JCV DNA sequences.…”
Section: Introductionmentioning
confidence: 99%